2020
DOI: 10.3345/cep.2019.01676
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic renal length and volume of normal Thai children versus their Chinese and Western counterparts

Abstract: Background: Renal size is an important indicator in the diagnosis of renal diseases and urinary tract infections in children.Purpose: The purpose of this study is twofold. First, it aimed to measure the renal length and calculate the renal volume of normal Thai children using 2-dimensional ultrasonography (2D-US) and study their correlations with somatic parameters. Second, it aimed to compare the age-specific renal size of normal Thai children with the published data of their Western and Chinese counterparts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…This may suggest a relationship between body height and renal length, especially with the left kidney which agrees with Rafat Saeed et al [9]. Our sonographic measurements of the kidney and spleen are correlated with previous studies [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultssupporting
confidence: 91%
“…This may suggest a relationship between body height and renal length, especially with the left kidney which agrees with Rafat Saeed et al [9]. Our sonographic measurements of the kidney and spleen are correlated with previous studies [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultssupporting
confidence: 91%
“…It is well known that kidney size (RL, RW, RT and RV) is related to age, height and weight. Almost all studies have shown that height correlates best with kidney length ( 10 , 13 , 15 , 16 ), and our findings support this conclusion, with height being the most relevant factor, followed by age and weight. Our results also showed that height correlated best with kidney width, thickness and cortical thickness, followed by age and weight.…”
Section: Discussionsupporting
confidence: 88%
“…Third, the use of RV to assess kidney size has a higher sensitivity and accuracy than the use of two-dimensional parameters (length, width and thickness). This is mainly due to the individual variability of kidney morphology and the fact that changes in twodimensional RSP caused by kidney disease are not as sensitive as changes in RV (13,14). However, RV measurement is not always available in some hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of normal kidney volume changes in growth and development of 321 Asian children, Rongviriyapanich et al found mean growth rates for the left and right kidneys of 11.48% and 7.66% per year, respectively, and mean increases in kidney volume of 8.60% per year for males and 11.45% per year for females [41]. In the control kidneys in the current study, the mean volume increases per year were 10.42% on the left side (n = 8) and 12.65% on the right side (n = 3), and males and females had mean increases of 9.91% and 11.96% per year, respectively.…”
Section: Discussionmentioning
confidence: 99%